2017
DOI: 10.1016/j.ekir.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Duration, Symptoms, and Disorders With Mortality in Adults With Chronic Kidney Disease

Abstract: IntroductionIn general populations, short and long sleep duration, poor sleep quality, and sleep disorders have been associated with increased risk of death. We evaluated these associations in individuals with CKD.MethodsThis was a prospective cohort study of 1452 NHANES 2005 to 2008 participants with CKD. CKD was defined by estimated glomerular filtration rate <60 ml/min per 1.73 m2 or urine albumin-to-creatinine ratio ≥30 mg/g. Sleep duration, sleep symptoms (difficulty falling asleep, difficulty staying asl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
1
17
0
7
Order By: Relevance
“…Extrapolation into the glomerular disease population seems relevant as this is a modifiable factor and can be applied broadly to all patients. 30 Weight reduction in obese patients may benefit glomerular diseases. [31][32][33] Small studies, focusing on diet and bypass surgery, have shown at least short-term benefits.…”
Section: Other Determinants Of Progression Of Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Extrapolation into the glomerular disease population seems relevant as this is a modifiable factor and can be applied broadly to all patients. 30 Weight reduction in obese patients may benefit glomerular diseases. [31][32][33] Small studies, focusing on diet and bypass surgery, have shown at least short-term benefits.…”
Section: Other Determinants Of Progression Of Kidney Diseasementioning
confidence: 99%
“…Established and emerging risk factors for progression of kidney diseaseRisk factors for progressive loss of GFR Emerging risk factors for progressive loss of GFR Prematurity (low birth weight) and other reasons for low nephron number29 Low-sleep duration and other related disorders (e.g., restless legs syndrome, sleep apnea)30 Obesity[31][32][33] Gender?34 GFR, glomerular filtration rate.…”
mentioning
confidence: 99%
“… 31 35 In nine studies (64.3%), the diagnosis of RLS was based on self-administered questionnaires, 4 , 36 38 ICD-9 codes, 5 , 39 and other sleep quesionnaires. 40 , 41 The results of 11 studies (78.6%) 4 , 5 , 31 34 , 36 , 37 , 40 , 41 supported RLS as a risk factor for increased mortality. The opposite conclusion was found in only three studies (21.4%).…”
Section: Resultsmentioning
confidence: 93%
“…Gangguan tidur terutama insomnia banyak dikeluhkan pasien hemodialisa dan membuat kualitas tidur yang buruk. Kualitas tidur yang buruk bisa membahayakan pasien karena akan meningkatkan risiko kematian dan kerusakan kardiovaskular pada pasien dengan penyakit ginjal kronis (CKD) (Ricardo et al, 2017).…”
Section: Pendahuluanunclassified